Pengaruh Metode Brain Endurance Training dan Motor Cognitive Training Terhadap Pengambilan Keputusan dalam Serangan pada Atlet Kumite Cabang Olahraga Karate - Anthony Paramadina Seda; Komarudin; Boyke Mulyana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to examine and compare the effectiveness of Brain Endurance Training (BET) and Motor Cognitive Training (MCT) using the Switched On Training application in enhancing dynamic decision-making ability among karate kumite athletes. A quantitative experimental method was employed with a Randomized Pretest-Posttest Control Group Design with Matched Subjects. The sample consisted of 30 cadet-junior kumite athletes (aged 14-17 years) homogeneously divided into three groups (BET, MCT, and Control) based on gender and weight class classifications. Static decision-making (decision-making traits) was measured using the Decision Style Questionnaire (DSQ), while dynamic decision-making was evaluated through recorded kumite match simulation, analyzed according to a standardized rubric. The results showed: (1) the participants' baseline cognitive profile was consistently dominated by Brooding (BET = 13,73; MCT = 12,64), Confident (BET = 13,73; Control = 13,00), and Spontaneous (BET = 12,55; MCT = 12,09) dimensions, with decision anxiety levels ranging from low to moderate; (2) for dynamic decision-making, the non-parametric Kruskal-Wallis test showed a statistically significant difference in overall Gain Score effectiveness across groups (Sig. = 0,003); (3) post-hoc Mann-Whitney U tests with Bonferroni Correction confirmed that the BET method was significantly superior to the control group (Sig. = 0,001); and (4) the MCT method showed no significant difference compared to the control group (Sig. = 0,200), while the comparison between BET and MCT indicated a trend favoring the BET group (Sig. = 0,053). It can be concluded that although athletes possess a baseline static decision style that is predominantly confident and spontaneous, Brain Endurance Training is the most effective intervention for maintaining the stability and effectiveness of attacking decisions in kumite athletes under conditions of mental fatigue. Keywords: Brain Endurance Training, Karate Kumite, Mental Fatigue, Motor Cognitive Training, Decision-Making